ACCOUNTING MEASUREMENT AND DISCLOSURE OF DEFERRED INCOME TAXES AND ITS ROLE IN IMPROVING THE QUALITY OF FINANCIAL REPORTING: AN APPLIED STUDY AT CIHAN BANK FOR INVESTMENT AND FINANCE - Hayder Oudah Kadhim; Zainab Hadi Mahdi; Hayder Kareem Salim (Scholar Express Journals, 2023)
The research aims to address an important issue of financial accounting, which is the measurement and accounting disclosure of deferred income taxes, and to demonstrate its role in improving the quality of financial reporting in a manner that is consistent with the changes accompanying the contemporary business environment, as well as positively affecting the decisions of internal and external users of accounting information. The research was applied in Cihan Bank for Investment and Finance for the period (2017-2020). The research reached a set of conclusions, the most important of which was that the accounting measurement and disclosure of deferred income taxes can help improve the quality of the information contained in the financial statements in a way that serves all users of this information. Reliance on it, and the management of the research sample banks understands the results that are reached as a result of measuring the quality of financial reporting, as well as the availability of sufficient time in these banks to measure the quality of financial reporting and provide appropriate information at the right time, in order to assist in making decisions at the appropriate times.
Keywords: Accounting measurement; disclosure of deferred income taxes; quality of financial reporting